Media-driven polarization: Evidence from the US - Mickael Melki; Petros Sekeris (Kiel Institute for the World Economy (IfW), 2019)
Using US data of media's coverage of politics and individual survey data, the authors document that in the states with a greater coverage of politics, citizens especially exposed to newspapers have more polarized preferences, partly coming from better political knowledge, and resulting in a higher political involvement measured as contributions to political parties and candidates.
http://dx.doi.org/10.7910/DVN/B52BHA
Keywords: K4; H0; 330; media; ideological polarization